Assessment of Metro Manila bus fare computation - Chavez, Sylvia A. Laborte (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
This research investigated LTFRB's bus fare computation methodology and assessed whether it is reasonable. Fares are considered reasonable if they are affordable to the passengers and at the same time sufficient to cover bus operating costs while providing the operator an adequate return on investment. LTFRB's first step in computing bus fare adjustment is to use the financial statements of ten big provincial bus companies and compute for fare adjustment rate which is based on its revenue deficiency ("Fare 1"). Then, fare adjustment rate is computed based on new fuel price ("Fare 2"). FAre adjustment is between Fare 1 and 2 adjustment rates. After reviewing LTFRB's computation methodology, relevant data were collected from Securities and Exchange Commission (SEC), 2010 Mega Manila Study, trading companies and some government agencies. The issues on present bus fare computation include basis of base fare and fare adjustment computation. Correlation analysis was performed on variable operating cost parameters, fuel price, historical fares, average income, etc. Base fare and fare adjustment rates were estimated using sample data from 2010 Mega Manila Study and SEC. Aside from being biased on big provincial bus companies, the analyses show that "Fare 1" adjustment computation is not reliable. On the other hand, "Fare 2" adjustment computation is reliable because of the strong correlation between fuel cost and operating costs. Likewise, study's estimate shows that the 2008 base fare is reliable.
Thesis (M.S. Civil Engineering, Transportation Engineering)--University of the Philippines, Diliman
Keywords: Bus lines -- Fares